Health-Related Quality of Life in Older Patients With Heart Failure From Before to Early After Advanced Surgical Therapies: Findings From the SUSTAIN-IT Study. (10th October 2022) - Grady, Kathleen L.; Kao, Andrew; Spertus, John A.; Hsich, Eileen; Dew, Mary Amanda; Pham, Duc-Thinh; Hartupee, Justin; Petty, Michael; Cotts, William; Pamboukian, Salpy V.; Pagani, Francis D.; Lampert, Brent; et al.
Abstract : Background: Restoring health-related quality of life (HRQOL) is a therapeutic goal for older patients with advanced heart failure. We aimed to describe change in HRQOL in older patients (60–80 years) awaiting heart transplantation (HT) with or without pretransplant mechanical circulatory support (MCS) or scheduled for long-term MCS, if ineligible for HT, from before to 6 months after these surgeries and identify factors associated with change. Methods: Patients from 13 US sites completed the EuroQol 5-dimension 3L questionnaire and Kansas City Cardiomyopathy Questionnaire-12 at baseline and 3 and 6 months after HT or long-term MCS. Analyses included univariate comparisons and multivariable linear regression. Results: Among 305 participants (cohort mean age=66.2±4.7 years, 78% male, 84% White, 55% New York Heart Association class IV), 161 underwent HT (n=68 with and n=93 without pretransplant MCS), and 144 received long-term MCS. From baseline to 3 months, EuroQol 5-dimension visual analog scale scores improved in HT patients without pretransplant MCS (54.5±24.3 versus 75.9±16.0, P <0.001) and long-term MCS patients (45.7±22.9 versus 66.2± 20.9, P <0.001); while Kansas City Cardiomyopathy Questionnaire-12 overall summary scores improved in all 3 groups (HT without pretransplant MCS: 47.2±20.9 versus 77.4±20.1, P <0.001; long-term MCS: 35.3±20.2 versus 58.6±22.0, P <0.001; and HT with pretransplant MCS: 58.3±23.6 versus 72.1±23.5, P =0.002). No further HRQOL improvement was found from 3 to 6 months. Factors most significantly associated with change in HRQOL, baseline 3 months, were right heart failure and 3-month New York Heart Association class, and 3 to 6 months, were 6-month New York Heart Association class and major bleeding. Conclusions: In older heart failure patients, HRQOL improved from before to early after HT and long-term MCS. At 6 postoperative months, HRQOL of long-term MCS patients was lower than one or both HT groups. Understanding change in HRQOL from before to early after these surgeries may enhance decision-making and guide patient care. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02568930.